The Realization Of Politeness Strategy Used By TheStudents In Sahid Tourism Institute Of Surakarta InPhatic Utterances: A Pragmatic Perspective - Purbasari, Kharisma Indah; , Dra. Siti Zuhriah Aryatmi, M.Hum; , Dr. Maryadi, MA (2016)
This research is about politeness in phatic utterances. This research has two objectives. The first objective of this reserach is to know the types of phatic used in Sahid Tourism Institute of Surakarta in Tourism Class and the second objective is to know the politeness strategies used in Sahid Tourism Institute of Surakarta in Tourism Class. The data are phatic utterances collected by using Discourse Completing Task (DCT) as the instrument. The data are analyzed by using theory of phatic types by Al-Qinai (2011) and theory of politeness by Brown and Levinson (2009). The research findings show that (1) phatic types that was found from the 9 scenarios are 12.1% of offering help, 6.4% of requesting, 13.8% of apologizing, 3.1% of grapping attention, 4,6% of suggesting, 13,8% of complimenting, 14,01% of thanking, 24,28 % of greeting, 2.7% of welcoming, 1,8% of reminding dan 3.7% of advising and (2) the politeness strategies that was found from the 9 scenarios are 59.11% of ORPP, 36.29% of ORNP, and 4.6% of BOR. Keyword: politeness strategy, phatic.